The Effect of Foreign Ownership, Investment Decisions, And Profitability on Company Value (Study on Companies Listed in the LQ45 Index on the Indonesia Stock Exchange for the Period 2019-2023) - Shendy Shendy; Wiwin Aminah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Firm value reflects investors' perceptions of a company's performance, often indicated by stock price movements and closely tied to how effectively management utilizes resources. This study examines the influence of foreign ownership, investment decisions, and profitability on firm value in companies listed in the LQ45 index on the Indonesia Stock Exchange during the 2019–2023 period. Employing a quantitative approach, secondary data were analyzed using panel data regression and descriptive statistics via Eviews 12. The sample, consisting of 22 companies selected through purposive sampling based on criteria such as consistent listing in LQ45 and data availability, may limit the generalizability of findings. Investment decisions were proxied by capital expenditure to total assets, profitability by return on assets (ROA), and firm value by Tobin's Q, while foreign ownership was measured as the percentage of shares held by foreign investors. The results show that foreign ownership, investment decisions, and profitability collectively influence firm value significantly. Partially, only investment decisions have a positive and significant effect. However, the study does not explicitly control for external shocks such as the COVID-19 pandemic, which may have affected financial performance and investor perception during part of the observation period. Future research should consider incorporating control variables for macroeconomic disruptions, expanding the sample size, or extending the study period. Practically, company management is advised to prioritize sound investment decision strategies to enhance firm value. For investors focusing on LQ45 stocks, attention to firms’ investment policies may serve as a reliable basis for valuation assessments.